Analisis Puisi “Yang Fana Adalah Waktu” Karya Sapardi Djoko Damono Dengan Pendekatan Struktural - Robby Rivaldo; Syahrul Faturrohman (Metonimia: Jurnal Sastra dan Pendidikan Kesusastraan, 2023)
Abstract Poetry is one of the literary works that has the best and dominant aesthetic function. This proves that poetry has meaning and meaning that is so beautiful. The study of poetry can be done in various aspects, one of which is by using a structural approach. In this research, it contains an analysis of the poem